Osteocalcin Alleviates Nonalcoholic Fatty Liver Disease in Mice through GPRC6A - Mingliang Zhang; Xiaomin Nie; Yeqing Yuan; Yansu Wang; Xiaojing Ma; Jun Yin; Yuqian Bao (International Journal of Endocrinology)
Osteocalcin is a bone-derived hormone that plays an important role in the crosstalk between bone and energy metabolism. Previous studies have found that treatment with uncarboxylated osteocalcin can protect mice from high-fat diet-induced nonalcoholic fatty liver disease (NAFLD). However, the potential mechanisms remain unclear. Although the G protein-coupled receptor family C group 6 subtype A (GPRC6A) is the putative receptor of osteocalcin, there is no direct evidence showing that GPRC6A mediates the effects of uncarboxylated osteocalcin in alleviating NAFLD in mice. We aimed to figure out this using liver-specific GPRC6A knockout (GPRC6ALKO) mice. Consistent with previous studies, uncarboxylated osteocalcin significantly protected high-fat diet-fed wild-type mice from obesity and NAFLD, while it did not protect high-fat diet-fed GPRC6ALKO mice from NAFLD. Differential mRNA expression of lipogenesis and lipolysis between GPRC6ALKO mice and control mice revealed that GPRC6A mediated the effects of osteocalcin in alleviating NAFLD through inhibiting lipid synthesis and promoting lipolysis. In conclusion, this study found that uncarboxylated osteocalcin alleviates NAFLD in mice through the GPRC6A signaling pathway. Our study suggests that liver GPRC6A may be a potential target for treating NAFLD.